Potential of diterpene compounds as antivirals, a review. Issue 8 (August 2021) - Wardana, Andika Pramudya; Aminah, Nanik Siti; Rosyda, Mila; Abdjan, Muhammad Ikhlas; Kristanti, Alfinda Novi; Tun, Khun Nay Win; Choudhary, Muhammad Iqbal; Takaya, Yoshiaki
Abstract: Viruses cause widely transmitted diseases resulting in pandemic conditions. Currently, the world is being hit by the Covid-19 pandemic caused by the SAR-CoV-2 infection. Countries in the world are competing to develop antivirals to overcome this problem. Diterpene compounds derived from natural ingredients (plants, corals, algae, fungi, sponges) and synthesized products have potential as antivirals. This article summarizes the different types of diterpenes such as daphnane, tiglilane, kaurane, abietane, pimarane, labdane, dollabelane, jatrophane, dolastane, prenylated guaiane, tonantzitlolone, casbane, have antivirals activity such as targeting HIV, Coxsackie virus, herpes virus, hepatitis virus, influenza virus, Chikungunya virus, Zika virus, dengue virus, and SARS-CoV. Some compounds such as andrographolide and its derivatives show promising activity in inhibiting the influenza virus. Additionally, compounds such as pineolidic acid, forskolin, sugiol, and many other diterpene compounds showed anti-SAR-CoV activity. The diterpene compound class's high antivirals potential does not rule out the possibility that these compounds can also act as anti-SAR-CoV-2 drugs in the future. Abstract : Antivirals, Covid-19, Diterpenes, Pandemic, SARS-CoV-2, Infectious diseases.